Have labour practices and human rights disclosures enhanced corporate accountability? The case of the GRI framework. Issue 1 (March 2018) - Parsa, Sepideh; Roper, Ian; Muller-Camen, Michael; Szigetvari, Eva
Highlights: Companies over-claim adherence to GRI reporting guidelines while failing to report detailed information on their workforce. Companies fail to provide material information. Limited evidence of companies acknowledging impediments they encounter when reporting on their workforce. Companies pay more attention to their internal (as opposed to their external) workforce. GRI fails to achieve enhanced comparability, transparency and accountability goals. Abstract: This paper critically evaluates Transnational Corporations' (TNCs) claimed adherence to the Global Reporting Initiative (GRI)'s 'labour' and 'human rights' reporting guidelines and examines how successful the GRI has been in enhancing comparability and transparency. We found limited evidence of TNCs discharging their accountability to their workforce and, rather, we found evidence to suggest that disclosure was motivated more by enhancing their legitimacy. TNCs failed to adhere to the guidelines, which meant that material information items were often missing, rendering comparability of information meaningless. Instead, TNCs reported large volumes of generic/anecdotal information without acknowledging the impediments they faced in practice.